2018
DOI: 10.3386/w24294
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Test, Non-actuarial Adjustments and Flexible Retirement

Abstract: We are grateful to Alexander Ludwig for advice on the computational algorithm. We thank Tabea ABSTRACTIn response to the challenges of increasing longevity, an obvious policy response is to gradually increase the statutory eligibility age for public pension benefits and to shut down pathways to early retirement such as special rules for women. This is, however, very unpopular. As an alternative, many countries have introduced "flexibility reforms" which allow combining parttime work and partial retirement. A k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As previously mentioned, the adjustment rate, , creates strong incentives for when to retire (Desmet & Jousten, 2003;Gruber & Wise, 2005;Fisher & Keuschnigg, 2010;Börsch-Supan, et al, 2017b). Occasionally, it is referred to as "actuarial adjustment rate," although the term "actuarial" only applies when is introduced in the pension system such that the present discounted value of participating in the pension system for all households is independent of their retirement age, R.…”
Section: Endogenous Retirement Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, the adjustment rate, , creates strong incentives for when to retire (Desmet & Jousten, 2003;Gruber & Wise, 2005;Fisher & Keuschnigg, 2010;Börsch-Supan, et al, 2017b). Occasionally, it is referred to as "actuarial adjustment rate," although the term "actuarial" only applies when is introduced in the pension system such that the present discounted value of participating in the pension system for all households is independent of their retirement age, R.…”
Section: Endogenous Retirement Decisionmentioning
confidence: 99%
“…Studies have shown that wealth and financial incentives have a great impact on retirement decisions (French, 2005;Chan & Stevens, 2008) as well as on the household composition and income status of individuals (Coile, 2004;van der Klaauw & Wolpin, 2008;Gustman & Steinmeier, 2004;Fuster, et al, 2003). The design of pension systems is of great importance for determining the impact on retirement behavior because individuals sometimes react strongly or weakly to changes in incentives and in the framework of pension systems (Gustman & Steinmeier, 2005;Duggan, et al, 2007;Kotlikoff, et al, 2007;Börsch-Supan & Schnabel, 1998;Gruber & Wise, 1999;Börsch-Supan, et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%